2021
DOI: 10.48550/arxiv.2111.11425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quasimaps to moduli spaces of sheaves on a K3 surface

Abstract: We continue the study of quasimaps to moduli spaces of sheaves, concentrating this time on K3 surfaces. We construct a surjective cosection of the obstruction theory for sheaves on K3×Curve, using the semiregularity map. The novelty of our considerations lies in the fact that we consider non-commutative fist-order deformations of the surface to prove the surjectivity of the semiregularity map. We then proceed to proving the quasimap wall-crossing formulae for reduced classes. As applications we prove the wall-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In (68) the sum over r is finite by Lemma 4.2, hence the statement of the theorem is well-defined. If a < 0 in Theorem 10.1, then taut = 0, so all Gromov-Witten invariants would vanish.…”
Section: Overviewmentioning
confidence: 90%
See 4 more Smart Citations
“…In (68) the sum over r is finite by Lemma 4.2, hence the statement of the theorem is well-defined. If a < 0 in Theorem 10.1, then taut = 0, so all Gromov-Witten invariants would vanish.…”
Section: Overviewmentioning
confidence: 90%
“…By Lemma 4.2 the series ( 58) is a Laurent polynomial in p. Proof. Denis Nesterov in [67,68] showed that the left hand side is equal to a partition function of relative Pandharipande-Thomas invariants of (S × C, S z ), see in particular [68,Cor.4.5]. The statement follows then from the GW/PT correspondence for (S × C, S z ) proven in [72, Thm.1.2] whenever β is primitive.…”
Section: Hilb/gw Correspondencementioning
confidence: 90%
See 3 more Smart Citations